Proposta de um modelo para identificação do nível de maturidade de aglomerados produtivos - Pietrobon, Fernandes (2009)
The present paper was developed aiming the raising of a maturity level identification process destined to clusters. A maturity identification model from the project area was taken and adapted clusters. The applied method was the in loco research, and the data gathering was taken by questionnaires with questions heading to the raising of this maturity identification system clusters. The case of Imbituva city cluster was studied as referral to validate this proposal. The questioned topics were: training, mapping out and standardization of processes, organization structure, strategic plan, continuous improvement, staff relation; certification; joint entures, organization, technology at the information. From the data obtained, the process was applied at the studied agglomerate. The results match with the agglomerate coordination’s opinion, showing coherence between the model and the reality. It is noticed that there are big growth opportunities to the studied cluster. Also it shows the necessity by other agglomerates to take this evaluation process to realize at what maturity level they are and what their improvement opportunities are.